2017
DOI: 10.1016/s2352-3018(17)30015-2
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling of HIV dynamics among transgender women: a respondent-driven sampling study in Rio de Janeiro, Brazil

Abstract: Background The burden of HIV in transgender women (transwomen) in Brazil remains unknown. We aimed to estimate HIV prevalence among transwomen, and identify the factors associated with newly diagnosed HIV infections. Methods “Transcender” was a respondent driven sampling study of transwomen in Rio de Janeiro, Brazil, conducted from August 2015 to January 2016. Twelve seeds were recruited from social movements and formative phase. Eligibility criteria were: self-identification as transwomen, being 18 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
1
28

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 31 publications
4
119
1
28
Order By: Relevance
“…We found that black racial identity, low income and unstable housing were associated with significantly lower odds of viral suppression. In the study overall (i.e., Transcender) and a recent study of MSM in Rio de Janeiro, newly diagnosed HIV infection was associated with non-white race [8,15]. And research from San Francisco has shown that housing instability [13] and low income [16] is associated with poor viral suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that black racial identity, low income and unstable housing were associated with significantly lower odds of viral suppression. In the study overall (i.e., Transcender) and a recent study of MSM in Rio de Janeiro, newly diagnosed HIV infection was associated with non-white race [8,15]. And research from San Francisco has shown that housing instability [13] and low income [16] is associated with poor viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…To participate, individuals had to self-identify as a transwoman, living in Rio de Janeiro or the metropolitan area, and be age 18 years or older. Details of the study methodology have been described elsewhere [8]. In brief, based on formative focus group findings, twelve seeds were selected to ensure that the sample was not over-represented by key variables, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for the association of non‐hormone use and HIV is not clear from our data. In other settings, lack of hormone use was associated with specific gender identities, such as “travesti” in Rio de Janeiro and “transsexual” in San Francisco , which in turn were groups with higher prevalence of HIV. These groups of transgender women may not be on feminizing hormone therapy because they cannot afford or do not desire the feminizing effects of oestrogen, thus transgressing gender norms in the trans and cisgender women communities.…”
Section: Discussionmentioning
confidence: 99%
“…We simulated HIV‐uninfected MSM and TGW at high risk of HIV infection in Brazil, modelling them as one population. While TGW experience a higher disease burden than MSM in Brazil , we combined the two populations because a PrEP programme in Brazil would likely target both. In the No PrEP strategy, individuals faced a monthly risk of HIV infection and were randomly tested for HIV at a rate of 4.4% per year (corresponding to a ~50% expected probability of being tested at least once over a lifetime) as per testing rates observed in this population in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…In 2007, 30.8% of those newly diagnosed with HIV infection reported sex with other men as the mode of HIV acquisition; by 2016, this proportion reached 50.2% . HIV risk is even more pronounced among TGW ; in Rio de Janeiro, Brazil, their HIV prevalence is estimated at 31.2% .…”
Section: Introductionmentioning
confidence: 99%